Notes on the wild cat Felis silvestris in Turkey (Mammalia, Carnivora) - Albayrak, Irfan (Annales. Series historia naturalis, 1997)
There was no specimen report on wild cat from Turkey for approximately 20 years. We are providing information on two specimens, both obtained in 1990's from the north-western Anatolia: a subadult male from Aydinpinar (skin and skull) and an unsexed skin from the vicinity of Yenice. In both cases the habitat was mixed or deciduous forest. Based on skull dimensions, Aydinpinar male appears too small for the subspecies F. s. caucasica but falls within the range of the nominate subspecies.
Keywords: divje mačke; favna; Turčija; Turkey